Analysis of the Implementation of Criminal and Administrative Offenses in the Perspective of Immigration Law Number 6 of 2011 (Case Study Djoko Soegiarto Tjandra) - Bima Yosua A Tarigan; Faridh Al Wajidi; K Karina (Journal of Law and Border Protection, 2020)
Criminal action is an act that violates the rules and punishable by crime, while the immigration administrative action is an administrative sanction given to foreigners outside the judicial process. One of the cases that have been in the public spotlight is the criminal case of Cessie Bank Balicorruption and bribery related to the deletion of the wanted list (DPO) by Djoko Tjandra. This study uses a qualitative empirical normative legal approach with data collection in the form of library materials which include statutory regulations, books, papers, and other sources. The formulation of the problem discussed in this study is how the application of criminal acts and Immigration Administrative Measures (TAK) in Law Number 6 Of 2011 concerning Immigration which is charged against Djoko Tjandra. The purpose of this research is to find out the criminal acts and administrative immigration actions given to Djoko Tjandra who was an Indonesian fugitive for many years. Based on the data analysis carried out, it was concluded that criminal and administrative actions ensnared Djoko Tjandra and the elements who helped him in accordance with the applicable rules, namely as the provisions written in the Criminal Code, Law Number 20 Of 2001 concerning the Eradication of Corruption Crime, and Law Number 6 Of 2011 concerning Immigration.